Analyis of the Implementation of Bedside Teaching in the Clinical Clership of Medical Professional Education - Andre Rattu; Deitje Adolfien Katuuk; Jeffry S. J. Lengkong; Tinneke E. M. Sumual (Yayasan Perguruan Kampus, 2026)
This study aims to examine the implementation of bedside teaching in clinical clerkships at the Faculty of Medicine, State University of Gorontalo, based on the perspectives of ten informants consisting of clinical supervisors and students. The study employed a qualitative approach using in-depth interviews, observations, and document analysis. Data were analyzed through reduction, presentation, and conclusion drawing to obtain a comprehensive understanding of the nine main indicators of bedside teaching. The findings show that in terms of planning, although it is already outlined in the curriculum and guidelines, implementation still faces coordination challenges between the faculty, teaching hospitals, and clinical supervisors. Bedside teaching has been carried out, but its effectiveness varies across teaching hospitals due to limited numbers of supervisors, short time allocation, and large student groups. Regarding medical interview and physical examination skills, most informants stated that the learning process follows academic theory, but is not yet optimal due to limited time and supervision. Students’ clinical decision-making skills remain low since most decisions are made directly by supervisors in line with hospital policies. Counseling, professionalism, and procedural skills are also taught but often constrained by hospital policies, limited patient availability, and insufficient time allocation. Overall clinical competence of students still heavily depends on supervisors, as no standardized policy has been applied across teaching hospitals. Bedside teaching evaluation is conducted through observation, clinical skills exams, clerkship reports, and case presentations, but some informants noted that evaluations focus more on final results, lack documentation, and provide minimal formative feedback. In conclusion, based on triangulation of information from ten informants, bedside teaching at the Faculty of Medicine, State University of Gorontalo has been implemented in line with the curriculum, but its effectiveness is not yet evenly achieved. Improvements should focus on strengthening coordination, increasing the number and quality of supervisors, standardizing policies across teaching hospitals, enhancing facility support, and developing a more consistent and continuous evaluation system.